2018
DOI: 10.3390/ijerph15020373
|View full text |Cite
|
Sign up to set email alerts
|

Young Women’s Perspectives of Their Adolescent Treatment Programs: A Qualitative Study

Abstract: The perspectives of at-risk adolescent clients can play an important role in informing treatment services. The current study examines qualitative interview data from 15 young women with histories of maltreatment. Using a semi-structured qualitative interview approach, we asked the women to think retrospectively about their treatment experiences as adolescent girls. Results highlight the need for providing adolescent girls with reliable and practical information about risky sexual behavior and drug use from rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While gender matching has often been seen as a stronger preference among young women than men, it may also be valued by younger men [82]. Some research has suggested that young people value clinicians who are similar to them in age, gender, and experience as this improves relatability [83]. Research investigating the impact of ethnicity matching on therapeutic outcome is varied, with one meta-analysis identifying small impacts of ethnicity matching on outcomes for most people and an overall decline in preference for ethnicity matching among adults in recent decades [84].…”
Section: Discussionmentioning
confidence: 99%
“…While gender matching has often been seen as a stronger preference among young women than men, it may also be valued by younger men [82]. Some research has suggested that young people value clinicians who are similar to them in age, gender, and experience as this improves relatability [83]. Research investigating the impact of ethnicity matching on therapeutic outcome is varied, with one meta-analysis identifying small impacts of ethnicity matching on outcomes for most people and an overall decline in preference for ethnicity matching among adults in recent decades [84].…”
Section: Discussionmentioning
confidence: 99%
“…The interview guide included broad, general questions designed to prompt respondents to think retrospectively about their adolescent years and to solicit information about the topics most important to them. The initial interview questions focused on the women’s prior treatment and intervention experiences (see Clark, Buchanan, & Leve, 2018 [ 37 ] for details). To gain a broad understanding of how adolescent girls choose romantic partners and partners’ influence on drug use and sexual behavior, we next asked general or hypothetical questions to create a pressure-free environment and provide an opportunity for respondents to give concrete examples.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on psychotherapy with youths indicate that outcomes are related to the way a therapist relates to patients. The therapist’s capacity to be non-judgmental and offer empathy, warmth, genuineness, honesty, flexibility, involvement, guidance, and instruction are particularly important [ 35 , 36 , 37 ]. Less is known about how the therapist’s skills and the therapeutic relationship affect a helping relationship [ 38 ].…”
Section: Introductionmentioning
confidence: 99%